Sales Management System - Bong Jing Yee; Syahida Hassan (Multidisciplinary Applied Research and Innovation, 2021)
Nowadays, online shopping has become essential due to Covid 19 restrictions. Small businesses are also proliferating to grab this opportunity of increasing their sales through online platforms. Although many have successfully implemented online businesses on multiple platforms, such as Instagram, Facebook, Lazada, and Shopee, many could not sustain their businesses as they do not have adequate tools to assist them with record keeping. Often, small businesses failed to keep track of their sales and revenue, which caused them to struggle with the growth of their business. Thus, this project aims to provide a tool for this target group by developing the Sales Management System (SMTS). SMTS is a web-based system that allows users to record information related to sales, products and suppliers. It can also generate sales reports. Rapid Application Development (RAD) was used as the methodology for this project, where we prioritise rapid prototype iterations. RAD has four phases, which are requirements planning, user design, rapid construction, and cutover. During the requirements planning phase, the requirements were gathered using the content analysis method where finding from past research was analysed to identify the problem and solution. Next, the low fidelity prototype was developed. SMTS was developed using JavaScript, HTML, CSS, MySQL, and PHP in the rapid construction stage. Upon completion, usability evaluation has been conducted to understand how users interact with the system. Improvements were made to the system based on the results. The system is hoped to provide a cheaper alternative in managing their data, consequently leading to better decision-making.